Analisis Adaptasi Sistem Informasi Manajemen dalam Mendukung Model Bisnis Berkelanjutan dan Green Economy - Dwi Febrina; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The development of green economy and sustainable business concepts increasingly requires companies to adopt strategies and systems that support environmental and social sustainability. Management Information Systems (MIS) play an important role in supporting this transformation by providing relevant data and information for strategic decision-making. This article analyzes the role and adaptation of SIM in supporting sustainable business models and green economy. This study uses literature review and conceptual analysis to identify key success factors for SIM adaptation in the context of sustainability. The findings suggest that a SIM integrated with green technology and sustainable business practices can improve a company's operational efficiency, transparency and environmental performance.